Geometry-induced modification of fluctuation spectrum in quasi-two-dimensional condensates - Arko Roy; D Angom (New Journal of Physics, 2016)
We report the structural transformation of the low-lying spectral modes, especially the Kohn mode, from radial to circular topology as harmonic confining potential is modified to a toroidal one, and this corresponds to a transition from simply to multiply connected geometry. For this we employ the Hartree–Fock–Bogoliubov theory to examine the evolution of low energy quasiparticles. We, then, use the Hartree–Fock–Bogoliubov theory with the Popov approximation to demonstrate the two striking features of quantum and thermal fluctuations. At T  = 0, the non-condensate density due to interaction induced quantum fluctuations increases with the transformation from pancake to toroidal geometry. The other feature is, there is a marked change in the density profile of the non-condensate density at finite temperatures with the modification of trapping potential. In particular, the condensate and non-condensate density distributions have overlapping maxima in the toroidal condensate, which is in stark contrast to the case of pancake geometry. The genesis of this difference lies in the nature of the thermal fluctuations.